PENGARUH KESEJAHTERAAN KARYAWAN, MOTIVASI KERJA, DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA RS BHAYANGKARA KOTA KEDIRI - Dhea Fatmala, Yossy; Sutapa, Heru; Yuni Astuti, Indah (Cahaya Ilmu Bangsa, 2025)
This study aims to determine the effect of employee welfare, work motivation, and training on employee performance at Bhayangkara Hospital Kediri. The research method used is a quantitative method with a descriptive approach. Data collection in this study was carried out by distributing questionnaires to employees of Bhayangkara Hospital Kediri and calculated using the SPSS Version 25 application. Data analysis techniques used include Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-test, F-test, and R2 Determination Coefficient Test. In the Validity Test, it is known that all question items (X1, X2, X3 and Y) have a significance value of 0.000 <0.05 so that each variable is declared valid. Then in the Reliability Test, each variable is declared reliable because it has a Cronbach's Alpha value> 0.60. Then in the t-test it is known that the variables of employee welfare (X1), work motivation (X2), and training (X3) have a significance value of 0.000 <0.05 so that the three variables partially have a significant effect on employee performance. Then in the F-test it shows that the results of the significance value are 0.000 <0.05 which indicates that employee welfare, work motivation, and training have a simultaneous effect on employee performance at RS Bhayangkara Kediri.